A methodology for quality-based mashup of data sources - Raza, Muhammad; Hussain, Farookh Khadeer; Chang, Elizabeth (Association for Computing Machinery (ACM), 2008)
The concept of mashup is gaining tremendous popularity and its application can be seen in a large number of domains. Enterprises using and relying upon mashup have improved their mass collaboration and personalization. In order for mashup technology to be widely accepted and widely used, we need a methodology by which can make use of the quality of the input to the mashup process as a governing principle to carry out mashup. This paper reviews the concept of mashup in different domains and proposes a conceptual solution framework for providing quality based mashup process.